Proposed new interior design scheme of Malaysian Paralympic Council office at No 5 Lorong Lengkok Harimau, Jalan Sultan Azlan Shah, 31400 Ipoh, Perak / Nur Aklili Riana Rozali - Rozali, Nur Aklili Riana (Faculty of Architecture, Planning and Surveying, 2011)
Every design stage should be completed thoroughly to ensure a successful of Malaysian Paralympic Council office design. The design objective of the project, site suitability, and the project requirements are analyzed to avoid lack of understanding that will lead to bad design. Other than that, the determining of concept and images play important parts in design as they act as guideline to the design proposal. If these factors are being neglected, there are possibilities for the Malaysian Paralympic Council office to be ignored by the public and left abandoned. In order to make sure a perfect design planning, the basic design aspects such as the comfort ability of each space, ergonomics and anthropometries, and psychological factors must be taken into consideration. At the same time, all of the data collections should be implemented in the design process so that the concept and image of excitement interior will be reflected in the design. Through the proposed new interior design scheme of Malaysian Paralympic Council office for Malaysian Paralympic Council will achieve its objective which is to create an easy access to the Malaysian Paralympic Council office which consider the requirement for each and every disabled person especially for those who are using wheelchair and the blinds.